2023
DOI: 10.1007/s10571-023-01345-5
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Communication Between the Brain and Other Organs: The Role of Extracellular Vesicles

Abstract: A number of substances released by the brain under physiological and pathological conditions exert effects on other organs. In turn, substances produced primarily by organs such as bone marrow, adipose tissue, or the heart may have an impact on the metabolism and function and metabolism of the healthy and diseased brain. Despite a mounting amount of evidence supports such bidirectional communication between the brain and other organs, research on the function of molecular mediators carried by extracellular ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 202 publications
0
10
0
Order By: Relevance
“…Interestingly, in the brain, all the cell types are able to produce and release EVs (Figure 2) that, once received by other cells, can modify their activities and properties both under physiological and pathological conditions [49,[107][108][109][110].…”
Section: Astrocytes and Bbb Formation And Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the brain, all the cell types are able to produce and release EVs (Figure 2) that, once received by other cells, can modify their activities and properties both under physiological and pathological conditions [49,[107][108][109][110].…”
Section: Astrocytes and Bbb Formation And Maintenancementioning
confidence: 99%
“…Interestingly, in the brain, all the cell types are able to produce and release EVs (Figure 2) that, once received by other cells, can modify their activities and properties both under physiological and pathological conditions [49,[107][108][109][110]. On the other hand, all the brain cells are also able to catch materials delivered through the EVs under both physiological and pathological conditions [110][111][112][113][114][115][116][117][118][119].…”
Section: The Role Of Extracellular Vesicles (Evs) In the Formation An...mentioning
confidence: 99%
“…Subsequent research revealed the existence of four main types of microbiota vesicles: OMVs, produced by outer membrane budding; outer inner membrane vesicles (OIMVs) and explosive outer membrane vesicles (EOMVs), produced by explosive cell lysis; and cytoplasmic membrane vesicles (CMVs), produced by Gram-positive bacteria [ 103 ]. Unfortunately, the precise mechanisms of the release of certain microbiota vesicles remain unclear [ 104 ]. Bacteria-derived EVs generally encompass lipids, nucleic acids, proteins, and other small molecules.…”
Section: Microbiome–gut–brain Axismentioning
confidence: 99%
“…Although orally administered EVs were distributed to the liver, lung, spleen, ovary, colon, kidney, pancreas, and finally the brain four days after administration, IV-administered EVs accumulate mostly in the liver [ 481 ]. The ability of EVs to cross the BBB bidirectionally [ 385 , 523 ] makes EVs attractive as nano-biocarriers for drug delivery to the brain. Betzer et al, 2017 found that intranasal administration of the EVs resulted in a significant degree of enrichment of EVs in the brain [ 524 ].…”
Section: Pharmaceutical Applications Of Extracellular Vesiclesmentioning
confidence: 99%